2003
DOI: 10.1074/jbc.m306786200
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles for Lipolysis and Oxidation in Peroxisome Proliferation-Activator Receptor Responses to Electronegative Low Density Lipoprotein

Abstract: Low density lipoprotein (LDL) exists in various forms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 39 publications
(57 reference statements)
1
42
0
2
Order By: Relevance
“…If this postulated mechanism is correct, the results indicate the presence of large amounts of some oxylipids in glycerides circulating in lipoproteins. Many other investigators have found significant amounts of esterified oxylipids in lipoproteins, and their presence has been postulated to play a role in atherogenesis [7][8][9]. The susceptibility of various oxylipid esters to various lipases has not been published, and we do not know what proportion of total esterified oxylipids was liberated during our experiment.…”
Section: Discussionmentioning
confidence: 73%
“…If this postulated mechanism is correct, the results indicate the presence of large amounts of some oxylipids in glycerides circulating in lipoproteins. Many other investigators have found significant amounts of esterified oxylipids in lipoproteins, and their presence has been postulated to play a role in atherogenesis [7][8][9]. The susceptibility of various oxylipid esters to various lipases has not been published, and we do not know what proportion of total esterified oxylipids was liberated during our experiment.…”
Section: Discussionmentioning
confidence: 73%
“…Fatty acids produced by LPL hydrolysis of VLDL (and to a lesser extent LDL and HDL) activate PPAR␣ and thus reverse the increase in vascular cell adhesion molecule-1 expression induced by inflammatory stimuli such as TNF-␣ and lipoproteins (65). In addition to highlighting a novel anti-inflammatory pathway, these findings suggest different transcriptional responses dependent on the specific mechanism of fatty acid generation and uptake (66).…”
Section: Potential Therapeutic Roles Of Ppar Agonists In Other Vasculmentioning
confidence: 84%
“…Previous studies have shown that LPL in combination with either triglyceride-rich lipoprotein or electronegative low density lipoproteins suppressed TNF-␣-induced cell surface adhesion molecule (VCAM-1) expression through peroxisome proliferator-activated receptor-␣ inhibition of NF-B activity (35,36). Peroxisome proliferator-activated receptor ligands are involved in anti-inflammatory effects (37,38).…”
Section: Discussionmentioning
confidence: 99%